16. OSTEOPOROSIS PREVALENCE AMONG POSTMENOPAUSAL WOMEN AGED 45 YEARS AND OLDER IN BAO LOC CITY, LAM DONG PROVINCE IN 2023 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the prevalence of osteoporosis among postmenopausal women aged 45 years and older in Bao Loc City, Lam Dong Province in 2023 and identify some related factors.Methods: A cross-sectional descriptive study was conducted from June 2022 to June 2023 on 303 postmenopausal women aged 45 years and older in Bao Loc city, Lam Dong province.Results: The prevalence of osteoporosis among postmenopausal women aged 45 years and older in Bao Loc city, Lam Dong province in 2023 was 13.5%. Factors significantly associated with osteoporosis included age, tea-drinking habits, and physical activity levels.Conclusion: Community-based studies assessing osteoporosis prevalence should be expanded, particularly targeting postmenopausal women aged 45 years and older, to enable early detection and preventive measures against osteoporosis-related complications.
Keywords: Osteoporosis; postmenopausal women; aged 45 and older; Bao Loc city; Lam Dong province